MASALAH EKSEKUSI PUTUSAN HAKIM PENGADILAN TATA USAHA NEGARA - Liliana Sysylia Darmono (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Indonesia as a democracy has a constitutional system that divides power into three parts, namely the legislative, executive and judicial branches to fulfill the principle of checks and balances. The form of control possessed by the judiciary is through a judicial institution which is empowered to provide legal protection and certainty. The State Administrative Court was established as a judicial institution based on Law Number 5 of 1986 with the aim of carrying out a prosperous, safe, peaceful and orderly state life, ensuring the position of citizens before the law and being able to maintain harmony. Balance and Harmony between State Administration Apparatus and Citizens. This research uses normative legal research which is carried out with descriptive analysis methods and uses a qualitative approach. The implementation of judicial proceedings has systematic problems related to the implementation of judicial decisions. Regarding the decisions of the PTUN judges, the problems faced are the enforcement of executions by revoking the KTUN, enforcement problems with forced money, administrative sanctions and problems sending decisions, which are social networks. announced. Currently, the implementation of the Administrative Court judge's decision faces several obstacles, which arise because the implementation of the decision is in the hands of the TUN officials. Some of the problems that arise are not clearly regulated and have a clear legal framework.